Post-Quantum Secure Design Principles for Detection and Mitigation in Critical Infrastructure Information Systems (International Journal of Scientific Research in Science and Technology, 2026)
The advent of quantum computing poses a significant threat to the cryptographic foundations that secure critical infrastructure information systems, including energy grids, transportation networks, healthcare systems, and financial services. Conventional public-key cryptographic schemes such as RSA and elliptic curve cryptography are vulnerable to quantum attacks, necessitating a paradigm shift toward post-quantum secure design principles. This review paper examines emerging post-quantum cryptographic frameworks and their role in strengthening detection and mitigation mechanisms within critical infrastructure environments. It systematically analyzes post-quantum algorithms, hybrid cryptographic models, and quantum-resilient authentication schemes, emphasizing their integration into intrusion detection systems, anomaly detection frameworks, and secure communication protocols. Additionally, the paper explores quantum-aware threat models, resilience-oriented system architectures, and adaptive mitigation strategies that enhance system survivability against both classical and quantum-enabled cyber threats. Key challenges including computational overhead, legacy system compatibility, scalability, and regulatory compliance are critically discussed, alongside ongoing standardization efforts and implementation case studies. By synthesizing current research and industry practices, this review provides a comprehensive roadmap for designing, deploying, and managing post-quantum secure detection and mitigation frameworks that ensure the long-term resilience, reliability, and trustworthiness of critical infrastructure information systems in the quantum era.